EchartsTag for chart generation using Taglib - Mamani-Pari, David (2021)
There are many tools for developing applications in Java, but there are few alternatives for frameworks or specialized libraries for displaying charts in web environments. Although most of them are for desktop environments, the PrimeFaces and ChartistJSF libraries are an alternative for the web, but they are oriented to projects based on Java Server Faces. In this sense, many projects prefer to use a graphics library built-in JavaScript, which implies an additional learning curve and is more time-consuming in developing applications. Therefore, it is necessary to have a unique graphics display library or framework for Java applications in the web environment. Therefore, in this article, it is proposed to build a tool that helps develop graphical visualizations in Java web projects using the concepts of TagLibs and Webjars. The proposed tool is called EchartsTag, and it was built following the XP methodology and validated with the SonarQube product and a group of professional experts in Java project development. EchartsTag is available on GitHub, so it can be used by any developer in the Java community or organizations that work with Java technology. Finally, the performance results of EchartsTag appear when compared with other alternative tools, achieving an average time of 14.17 minutes in development time and occupying third place in average viewing time that is 3.5ms after Chartjs and HighChats. In addition, to occupy the first place in evaluating other criteria for java web development with charts tools.